Pertumbuhan Bruguiera gymnorrhiza pada Sistem Silvofishery di Desa Simpang Tiga Jaya Kecamatan Tulung Selapan Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Lensari, Delfy; Hustati, Sasua; Rahmad, Beni; Rasyid; Harefa, Ribka (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to examine and analyze the effects of pond planting sites and riparian area planting sites on the growth and development of Bruguiera gymnorrhiza seedlings, as well as to evaluate the survival and growth performance of seedlings originating from propagules compared to those naturally collected from the wild. A quantitative experimental method was employed in this research. The research data were analyzed using ANOVA. The findings indicate that the growth performance of Bruguiera gymnorrhiza seedlings in pond planting sites was superior to that in riparian planting sites with respect to plant height, stem diameter, number of leaves, and root length. Furthermore, seedlings derived from propagules demonstrated better growth outcomes compared to those collected from the wild, particularly in terms of plant height, stem diameter, number of leaves, root development, and survival rate.